UPAYA PENINGKATAN KEMAMPUAN MATEMATIKA SISWA SMA NEGERI 8 KOTA BENGKULU DALAM MENGHADAPI OLIMPIADE SAINS - Dian Agustina; Etis Sunandi; Herlin Fransiska (DHARMA RAFLESIA, 2018)
The objectives of this dedication program is to build up and to guide the students in understanding, analyzing, and solving the problem in Mathematics Olympic, thus they know the strategies and the quickest way to solve the Olympic question precisely. This program is also to prepare the students participating the mathematics Olympic to get more competitive in higher level. The methods used in this dedication program are collecting the materials and the latest Olympic paper test, selecting potential students in mathematics, pre-testing, building up, and post-testing. One of the result of this dedication program showed that the knowledge of SMAN 8 Kota Bengkulu students toward mathematic Olympic was good, moreover some students have participated Mathematic Olympic in junior high level. Keywords: Olympic, mathematic, SMAN 8 Kota Bengkulu